Classification of Language Means Expressing Time Relationship - Sheraliyeva Dilnoza Qurvonali qizi; Mamajonov Alijon (Zien Journals, 2023)
In this article, language and period-specific terms are explained; the study of period-specific relations and their importance in linguistics, the role of linguistic tools expressing the period relationship in the text are analyzed on the example of excerpts from various works.
Keywords: Language; linguistic means of expressing time relations; adjunct